Flavonoids as Multi-Target Compounds: A Special Emphasis on their Potential as Chemo-adjuvants in Cancer Therapy - Namdeo, Ajay G.; Boddu, Sai H.S.; Amawi, Haneen; Ashby Jr., Charles R.; Tukaramrao, Diwakar B.; Trivedi, Piyush; Babu, R. J.; Tiwari, Amit K. (Current Pharmaceutical Design, 2020)
Flavonoids are low molecular weight, polyphenolic phytochemicals, obtained from secondary metabolism of various plant compounds. They have a spectrum of pharmacological efficacies, including potential anticancer efficacy. Natural flavonoids are present in fruits, vegetables, grains, bark, roots, stems, flowers, tea and wine. Flavonoids can attenuate or inhibit the initiation, promotion and progression of cancer by modulating various enzymes and receptors in diverse pathways that involve cellular proliferation, differentiation, apoptosis, inflammation, angiogenesis and metastasis. Furthermore, in vitro, flavonoids have been shown to reverse multidrug resistance when used as chemo-adjuvants. Flavonoids (both natural and synthetic analogues) interact with several oncogenic targets through dependent and independent mechanisms to mediate their anticancer efficacy in different types of cancer cells.
Keywords: secondary metabolism